The Crime of Prostitution in View of the KUHP and Law No. 19 Year 2016 - Sitompul, Ariman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Sex work through social media has now become a criminal problem that is often encountered through social media, Instagram, WhatsApp, Facebook, and other applications such as micat and tantan. This happens with the increase in a person's lifestyle or economic problems. Proof of criminal law in cyber crimes in the form of commercial sex workers through social media is the focus of this research. The type of legal research carried out is normative juridical, so the approach used is the Statute approach and the conceptual approach. Evidence of cyber prostitution is the same as Article 184 of the Criminal Procedure Code, namely regarding evidence in the form of witness statements, expert statements, letters, instructions. However, in the ITE Law, cases that become evidence can be said to be digital evidence because they are in the form of electronic information and/or electronic documents in accordance with the criteria in Article 1 number 1 and number 4 of Law Number 19 of 2016 so that this digital evidence can clarify facts that have occurred supported by other evidence.